Ensino em ciências: a prática e a formação do professor que atua nos anos iniciais do ensino fundamental na cidade de Santarém - Pará - PEREIRA, Williana Rêgo (Universidade Federal do Oeste do Pará, 2024)
Teaching science in the early grades is still a challenge for teachers, as the use of traditional methodologies arouses little interest in students. In this context, changes in the teaching scenario through the use of other methodologies are fundamental to arouse students' interest in science, research and study. Given this, the present work aimed to conduct a methodological discussion on science teaching in the early years of elementary school, reflecting a little on the methodologies applied in the classroom and teacher education. To achieve this goal, the following question was used: “How could the teacher organize the teaching strategies in order to enable the student to build / reconstruct their scientific knowledge?”. Next, an analysis of teacher education was promoted from the methodologies applied in science classes. This study was conducted with teachers from 1st to 5th grade of elementary school in a private school in the city of Santarém-Pará. Questionnaires were applied to the teachers of this school space, through which we tried to debate about the methodology of teaching-learning in science applied in that school. The results of these questionnaires demonstrate that the teachers interviewed use various learning and assessment methods, which are concerned with the learning of their students and always look for a way to teach a more playful and interesting class, so that their students can be interested in subject covered. Research has shown that these teachers are looking for formative assessment to vary their assessment tools. Thus, it is concluded that the great challenge of the pedagogical practice in the early years is the investment in the process, the differentiated look of the parents, the respect with the particularity of each student, and the awareness of the role of teacher in being responsible for the necessary changes for overcome every day the challenges that the classroom can bring you.